2020
DOI: 10.3390/met10111551
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Leidenfrost Temperature in Spray Cooling for Continuous Casting and Heat Treatment Processes

Abstract: Spray cooling of hot steel surfaces is an inherent part of continuous casting and heat treatment. When we consider the temperature interval between room temperature and for instance 1000 °C, different boiling regimes can be observed. Spray cooling intensity rapidly changes with the surface temperature. Secondary cooling in continuous casting starts when the surface temperature is well above a thousand degrees Celsius and a film boiling regime can be observed. The cooled surface is protected from the direct imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Spray cooling of hot steel surfaces is an indispensable part of continuous casting and heat treatment [11,12]. The spray cooling rate must be dynamically controlled to maintain competitiveness and continuously produce high-strength, high-quality steel at the highest productivity during continuous casting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spray cooling of hot steel surfaces is an indispensable part of continuous casting and heat treatment [11,12]. The spray cooling rate must be dynamically controlled to maintain competitiveness and continuously produce high-strength, high-quality steel at the highest productivity during continuous casting.…”
Section: Introductionmentioning
confidence: 99%
“…Now that rapid quenching is crucial to achieve excellent mechanical properties of materials, it is also essential to precisely predict and control the LFP. Even if the LFP has a clear definition, it is (in the case of spray cooling) challenging to automatically read it from experiment data [11]. In this research, the water-air spray cooling of a hot metallic surface with different initial temperatures (600℃, 650℃, 700℃, 750℃, 800℃, 850℃, and 900℃) is studied.…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic and pneumatic nozzle cooling is widely used in the secondary cooling of continuous casting as it provides a good balance in terms of its ability to remove high heat fluxes, efficiently uses liquid and obtains good uniformity in the temperature of the solidified product. Therefore, several researchers have studied parameters such as impingement density, w [1][2][3][4][5][6], speed and droplet size [2,[4][5][6][7], distance between the nozzle and the part to be cooled [3,8], roughness [2,9] and the spray angle [10], among others, since these modify the way in which the nozzles extract heat, furthermore Kominek et al [11] found that the choice of nozzles and their overlaps has a significant influence on cooling homogeneity. However, poor heat extraction can cause the appearance of defects such as internal or surface cracks that influence the quality of the solidified products [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Arth et al [13] mention that the casting speed is dependent on the impingement density. Many researchers agree that impingement density is the parameter that has the most influence on the cooling stage [4,[20][21][22][23][24] and therefore, should be taken into consideration when designing the secondary cooling nozzle arrangement. For this reason, the main aim of this research is to analyze the impingement maps produced by two hydraulic nozzles and to quantify the heat extraction in the stainless-steel plate varying the operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient water-spraying in the secondary cooling zone is an important CC topic. Recently, Hnizdil et al [30] worked out an improved prediction of the Leidenfrost temperature. Kotrbacek et al [31] combined experimental investigations to adjust the classical estimation of the HTC by introducing a correlation function [31].…”
Section: Introductionmentioning
confidence: 99%